Dekokta Scurulla atropurpurea Terhadap Kelengkungan Tulang Belakang Embrio Ikan Zebra - Nour Athiroh (Universitas Islam Negeri Mataram, 2018)
Toxicity study on herb Scurulla atropurpurea has done by using Zebra fish (Danio rerio) embryo. The objective of this research is to study the effect of decocta of parasitic tea leaves on theraphy dosage, MATC, and LC50 to the backbones of Zebra fish embryo. This research is done by laboratory experiment method through in vitro by using research design post randomized control group only. The animal used in this research is Zebra fish embryo less than 3 hours post fertilization after fission process is finished and embryo is entering blastula stage. Total number of sample is 80 embryo and divided into 4 groups: control group without treatment, therapy dosage group (200ug/ml), LC50 group (2066ug/ml) and MATC group (237ug/ml) by decocta of parasitic tea leaves. Sample of Zebra fish embryo is putting in well-plate with 1 embryo per well. Treatment was given untill embryo at 72hpf at temperature 270 C. Data taken during study is analysed using one way ANOVA by SPSS version 16. Treatment with therapy dosage 200, MATC 237 and LC50 of decocta of parasitic tea leaves do not cause curvature of backbone in Zebra fish embrio. It is suspected that active compound in decocta of parasitic tea leaves at all above dosage do not able to disturb the structure and function of backbone.